Online Gaming Addiction as a Psychosocial Disorder in Children: Impact, Factors, and Management Strategies in Sidorame Timur Village, Medan, North Sumatra - Siregar, Muhammad Fath Linnas; Metia, Cut (TEMALI : Jurnal Pembangunan Sosial, 2025)
Rapid advances in digital technology have led to a significant increase in the intensity of online gaming among children, particularly at the elementary school level. This study aims to examine the psychological impact of online gaming addiction on children in Sidorame Timur Village, Medan Perjuangan District, North Sumatra Province, identify the contributing factors, and explore the response patterns exhibited by parents. This study employs a qualitative approach with a case study design, involving in-depth interviews and direct observations of eight children aged 11–12 years who exhibit symptoms of online game addiction, along with their parents. Data analysis was conducted using a thematic approach. Findings indicate that online game addiction has negative effects on children’s psychological well-being, such as learning concentration disorders, anxiety, sleep dysfunction, and reduced social interaction. Key factors contributing to addiction include poor communication between parents and children, the diversity of evolving game types, and peer social pressure. In response to this situation, some parents have begun to adopt open communication patterns, establish more structured schedules, conduct active supervision, and encourage their children to participate in social and physical activities. This study emphasizes the importance of strengthening digital parenting capacity at the family level as a preventive measure against online game addiction. These findings provide practical contributions to the development of digital literacy-based education policies and community-based intervention programs. The uniqueness of this study lies in its in-depth exploration of addictive behavior and parenting strategies in a local context, offering contextual insights into the study of child psychology and education in the digital age.